The Prospect of the Existence of National Criminal Code in a Democratic State in Indonesia during the Covid-19 Pandemic - Suharyo Suharyo (Jurnal Penelitian Hukum De Jure, 2021)
The Dutch colonial product Criminal Code which has been translated into various versions remains valid in Indonesia, because the plenary session of the House of Representatives of RI for the 2014 – 2019 period which was attended by government elements to ratify Draft Criminal Code to become the National Criminal Code was postponed due to refusal from students and civil society movements. The Covid-19 pandemic as a health and humanitarian disaster that destroyed almost all aspects of human life, throughout the world including in Indonesia with various long-lasting negative impacts, in 2020 until now has thwarted legal development including realizing the National Criminal Code. This research was conducted in a sociological juridical manner, with the issue of whether the Draft Criminal Code would be re-discussed in several articles, and then ratified by the House of Representatives of RI. How to respond to the social action reactions of a group of people who are expected to persist, even though the Draft Criminal Code is re-discussed on a limited basis, and is expected to hold demonstrations and rallies, as well as what are the prospect of the existence of the National Criminal Code in the Covid-19 pandemic era. The government continues to receive and select input or suggestions from various community groups regarding crucial issues. What is certain is that if there is a rejection of the Draft Criminal Code to be ratified, it must be returned to the constitution in force in the Unitary State of the Republic of Indonesia, namely through a judicial review lawsuit at the Constitutional Court of the Republic of Indonesia.